Penetapan Kadar Total Fenolik dan Flavonoid Ekstrak dan Fraksi Ekstrak Kulit Buah Pepaya Muda (Carica papaya L.) - Tunik Saptawati; Annisa Dea Ardani; Firstca Aulia Rachma; Sri Suwarni (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Papaya peel (Carica Papaya L.) is a plant that has several pharmacological activities because it contains secondary metabolites in the form of phenolics and flavonoids. This study aims to determine the total phenolic and flavonoid levels in the extract and fraction of papaya peel using the colorimetric method. The research method for determining total phenolic content with the Folin-Ciocalteu method, using gallic acid as a comparator, and the determination of total flavonoid content using the AlCl3 complex formation method with quercetin as a comparator, both using UV-Visible spectrophotometry. The results of the total phenolic content of the ethanol extract of papaya peel, the water fraction of papaya peel, the ethyl fraction of papaya peel, and the n-hexane fraction of papaya peel were 79.6393%, 65.5173%, 84.5257%, and 48.0085%, respectively. The results of the total flavonoid content of the ethanol extract of papaya fruit peel, the water fraction of papaya fruit peel, the ethyl acetate fraction of papaya fruit peel, and the n-hexane fraction of papaya fruit peel were 55.1744%, 33.2677%, 87.2572%, and 21.1696%, respectively. Based on these results, it can be concluded that the greatest total phenolic and total flavonoid content was in the ethyl acetate fraction of unripe papaya fruit peel extract.